A case study about community college support practices for first-year, first-generation community college student-athletes - Worrels, Derrick L. (My University, 2025)
The National Junior College Athletic Association (NJCAA) oversees athletics at 525 community colleges, involving approximately 70,000 student-athletes annually. Many of these athletes are first-generation college students (FGCSs), a demographic that constitutes almost two thirds of all students at two-year institutions. However, data on the percentage of first-generation student-athletes at community colleges are scarce. These students often come from low-income families with limited exposure to higher education and face unique challenges, including academic preparedness, time management, financial constraints, and social integration. Despite their recruitment for athletic performance, many first-year, first-generation student-athletes fail to persist beyond their first year. The purpose of this qualitative single-case study was to gain an understanding of the college support practices provided by community colleges to enhance the involvement of first-year, first-generation student-athletes. Findings revealed that while general support systems exist for student-athletes, few practices are tailored specifically to FGCSAs. Themes that emerged across institutional departments included the need for improved data tracking, expanded mental health services, mentoring from coaches and peers, and the benefits of programs like TRIO and intrusive advising. Faculty, staff, and leadership cited a strong culture of care and collaboration, though acknowledged gaps in targeted support and disaggregated data collection. Recommendations include the implementation of FGCSA-specific advising, structured mentoring programs, and partnerships to extend wraparound support services beyond the athletic sphere.
Keywords: First generation community college student athlete